Evolution of spectral lines under time-dependent illumination of an absorbing and scattering atmosphere - Nikoghossian, A.
This is a continuation of the author’s research on the temporal variations in the spectral line profiles formed in absorbing and scattering atmospheres illuminated by non-stationary energy sources. The line radiation transfer in an atmosphere of finite optical thickness is considered under assumption of complete frequency redistribution. We treat two types of illumination of the medium: the sources of the form of Dirac δ(t) and Heaviside H(t) unit jump functions. The goal of the work is to identify the dependence of the dynamics of changes in the spectral line profiles on frequency redistribution and the values of various optical parameters such as the optical thickness of the medium and the value of scattering coefficient. It is shown that in some cases this dependence allows to use observational material on dynamics of the burst phenomena to estimate some of these characteristics.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture